Promotion of new technologies by European regional development agencies - The case of Austria. - Sabine Sedlacek; Veronika Gaube (European Regional Science Association (ERSA), 2002)
According to the current focus of the regional policy of the European Union on sustainable regional development the question arises - what are the key-elements to achieve a sustainable regional pathway? The identification of these key-factors is a challenge for the regional policy in each member state. One elementary key-factor is the promotion of new technologies as part of a regional innovation strategy. Regional institutions which support environmental improvements within regions can be identified as key-actors for achieving a sustainable regional pathway. This contribution focuses mainly on the analysis of these institutions within Austrian regions that are analysed within a research project funded by the Austrian National Bank ("Jubiläumsfonds der Österreichischen Nationalbank"). The main objectives are the following: (a) Identification of those institutions relevant for fostering new technologies to achieve a sustainable regional development. (b) Typology of these institutions to gain an appreciation of the relevant policies and activities of the regional development agencies in regions in fostering within companies new technologies which support environmental improvements, both in their own regions and elsewhere in the European Union. (c) Analysis of the institutions activities (activity profiles) (d) To foster an exchange of information on policy in these activities between the agencies. (e) Identification of network activities between different types of regional institutions. The main research question focusses on the relevance of existing regional institutions and their ability of fulfilling the challenges of sustainable regional development goals. Their role within the regional innovation system and their flexibility to change their target group profiles seems relevant for successful applications of sustainable regional development strategies. The question of the relevance of completely new types of institutions or only adapted profiles of still existing institutions needs to be answered. The paper will focus on the Austrian institutional landscape. Several types of regional institutions will be analysed within a survey based on standardised questionnaires. Within a second step of analysis those types of institutions with explicitly focuses on sustainable regional projects will be further analysed with in-depth case studies.
Keywords: 330